Experience in the Use, Evaluation of the Effectiveness and Safety of Regional Anesthesia Techniques - Valievich, Khalilov Firuz; Valentina, Sevagina; Yuiryevna, Goncharova Tatyana; Kamilovich, Kaibov Akim (International Journal of Psychosocial Rehabilitation, 2020)
Providing pain relief and eliminating the painful sensation of pain are of paramount importance in medicine and anesthesiology. Currently, the undeniable advantages those regional methods of anesthesia have allowed using this method of anesthesia more often in medical practice.With the introduction in clinical practice of means of delivering drugs directly to the place of their action, the use of epidural RSA, the development of combined spinal-epidural anesthesia, as well as the synthesis of new low-toxic local anesthetics, regional methods of anesthesia have taken a significant place in the overall structure of anesthesia. That determines the relevance of this article.